Flashpoints for Asian American studies - Schlund-Vials, Cathy J., 1974-; Nguyen, Viet Thanh, 1971- (Fordham University Press, 2018)
Born out of mid-century social movements, Asian American studies is now an established field of transnational inquiry, diasporic engagement, and rights activism. These histories serve as initial moorings for Flashpoints for Asian American Studies, a collection which considers the contemporary possibilities of and limitations inherent in Asian American studies as historically entrenched, politically embedded, and institutionally situated interdiscipline.